Microwave Assisted Synthesis, Characterization and Anti-Tubercular Activity of 4-Quinolylhydrazone - Bisen, Chandrakant V.; Patle, M. R.; Rahangdale, P.K. (Journal of Drug Delivery and Therapeutics, 2019)
A series of 4-quinolylhydrazone derivatives was synthesized by reaction of 4-quinolylhydrazine and various substituted carboxaldehyde out of that most of the derivatives show significant antitubercular properties. The microwave assisted organic synthesis was applied to synthesize a series of 4-quinolylhydrazone derivatives. The characterizations of newly synthesized derivatives were done by modern analytical techniques like digital melting point apparatus, IR, NMR and mass spectroscopy.Keywords: Mycobacterium tuberculosis, Hydrazone, Quinoline, Carboxaldehyde.